Programmed cell death protein 1 inhibitors in advanced cutaneous squamous cell carcinoma: real-world data of a retrospective, multicenter study - Salzmann, Martin; Leiter-Stöppke, Ulrike; Loquai, Carmen; Zimmer, Lisa; Ugurel, Selma; Gutzmer, Ralf; Thoms, Kai-Martin; Enk, Alexander; Hassel, Jessica C. (European journal of cancer, 2020)
Background: Cutaneous squamous cell carcinoma (cSCC) is one of the most common malignancies of the skin. Even though most patients are sufficiently treated by surgical resection, some will eventually metastasize and need systemic therapy. Phase I and II studies have shown efficacy for programmed cell death protein 1 (PD-1) inhibitors, but cohort sizes are low and real-world data especially on long-term outcome are pending. Methods: Patients from six German skin cancer centers treated with PD-1 inhibitors (pembrolizumab, nivolumab or cemiplimab) for advanced cSCC were retrospectively studied. Internal patient records were analyzed for clinical outcome including response, progression-free survival (PFS), overall survival (OS) and toxicity. Results: Of 46 evaluable patients (median age: 76 years), the overall response rate (RR) was 58.7%, including 15.2% with complete response. The disease control rate was 80.4%. Both median PFS and OS were not reached, Kaplan-Meier estimated 1-year PFS was 58.8%. Patients responding to therapy showed durable remission. Response was independent of the PD-1 inhibitor used and also independent of the presence of distant metastases vs. locally advanced disease. Two predictive factors were found: Patients with primaries located on the leg had a poorer therapy outcome and patients with high lactate dehydrogenase serum levels at baseline. Treatment was overall tolerated well, with less than 10% of patients discontinuing therapy due to toxicity. Conclusions: PD-1 inhibitors fulfill the need for an efficient systemic therapy for advanced cSCC and should be the new standard of care. With high RRs and durable disease control, neoadjuvant and adjuvant regimens should be evaluated. (C) 2020 Elsevier Ltd. All rights reserved.
Gesehen am 11.12.2020